Biópsias pulmonares percutâneas guiadas por imagem: experiência de um hospital geral - Correa, Jose Roberto Missel (2013)
Introduction : The lung biopsies guided by computed tomography (CT ) , either by aspiration or removal of tissue fragments , the procedure is routinely performed in developed countries , with proven specificity , accuracy and sensitivity in the diagnosis of pulmonary lesions . In Brazil , there are few published studies reporting the use of image -guided percutaneous biopsy aimed at the diagnosis of lung diseases . Objective: To describe the epidemiology and outcomes of pathological lesions suspected of malignancy in patients undergoing image-guided lung biopsy at the University Hospital of Santa Maria ( HUSM ) . Material and Methods: A descriptive cross-sectional study conducted from January 2007 to January 2012 , the Department of Radiology and Diagnostic Imaging , University Hospital of Santa Maria . Results: We analyzed data from 36 patients undergoing biopsy guided by computed tomography ( CT) or ultrasound (US), 25 men and 11 women , mean age 63 years ( 35-80 years) and history of smoking in 80% of patients . The average lesion size in diameter was 6.3 cm (1.5 to 18.2 cm) and 20% of patients had signs of pulmonary emphysema. In pathology , 53 % showed non-small lung cancer cells , 5.5% of small cell lung cancer , 25 % negative sample , 3 % and 14 % inconclusive other malignancies . As a case complication of pneumothorax was observed (2.8 %). Conclusion : The results suggest that image - guided percutaneous biopsy was performed in most middle-aged adults and elderly , male , smokers and non-small cell bronchial tumor . As it is a minimally invasive procedure with high accuracy in the diagnosis of lung diseases and low rate of complications , it is the indication for suspected lung injury.